2020
DOI: 10.1037/apl0000655
|View full text |Cite
|
Sign up to set email alerts
|

Getting back to the “new normal”: Autonomy restoration during a global pandemic.

Abstract: We investigate the psychological recovery process of full-time employees during the 2-week period at the onset of the Coronavirus pandemic (COVID-19). Past research suggests that recovery processes start after stressors abate and can take months or years to unfold. In contrast, we build on autonomy restoration theory to suggest that recovery of impaired autonomy starts immediately even as a stressor is ongoing. Using growth curve modeling, we examined the temporal trajectories of two manifestations of impaired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 103 publications
2
50
1
Order By: Relevance
“…Our research contributes to the growing literature on the psychological effect of COVID-19. While the majority of such research has examined the emotional distress engendered (e.g., [45,46]), fewer have examined effects on individuals' sense of self [47][48][49] and social identities [7,8]. We explicitly investigate how COVID-19's disruptions to social systems and social roles can undermine self-authenticity.…”
Section: Contributions and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our research contributes to the growing literature on the psychological effect of COVID-19. While the majority of such research has examined the emotional distress engendered (e.g., [45,46]), fewer have examined effects on individuals' sense of self [47][48][49] and social identities [7,8]. We explicitly investigate how COVID-19's disruptions to social systems and social roles can undermine self-authenticity.…”
Section: Contributions and Implicationsmentioning
confidence: 99%
“…Indeed, past research related to authenticity under COVID-19 does so by way of autonomy, specifically, autonomy in the workplace. Anicich et al [47] find that COVID-19 weakens employees' sense of autonomy ("I feel like I am able to truly be myself right now"), while Dobson [62] finds that working from home in COVID-19 enhances workers' autonomy and authenticity. One way to interpret these results is that preserving autonomy can safeguard authenticity.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Scholars can assess variability in power states over time (i.e., power fluctuation) in two ways. The first method involves asking participants to report their momentary sense of power each day (or multiple times per day) over multiple days (e.g., “Right now, I feel powerful”; see Anicich et al., 2020) using an experience sampling or daily diary design and then estimating the standard deviation (SD) of the reports for each person. The only two papers to date that have explicitly assessed power fluctuation used this method (Anicich et al., 2021; Sabey et al., 2020).…”
Section: Methodological Obstacles and Opportunities Related To Middle Powermentioning
confidence: 99%
“…Meanwhile, Anicich et al (2020) investigated the process of psychological recovery of full-time employees Work-related stress and employee engagement among millennial workforce in the new normal…”
Section: Millennial Workforce During Covid-19 Pandemicmentioning
confidence: 99%
“…Evidently, Chillakuri and Mogili (2018), Plamann (2019), and Rivers (2018) postulated that the millennial generation differs from the previous generations in terms of workplace behavior, outlook, perspective, motivation, and loyalty, as well as, reason for leaving and job satisfaction. Additionally, Anicich, et al (2020) and the Deloitte Global Millennial Survey 2020, revealed that the millennial workforce displayed a marked resiliency in terms of recovering through the pandemic, considering them as a "resilient generation" holding the key to a better normal. Meanwhile, Codd (2020) mentioned that even before the pandemic, a substantial number of millennial and Gen Z workers were experiencing stress and anxiety most of the time.…”
Section: Synthesismentioning
confidence: 99%